Komentarji novic regionalobala.si med govorjenim in pisnim diskurzom: Maša Rolih (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Regionalobala.si News Comments Between Spoke and Written Discourse. The enormous technological progress of the digital and networked society has enabled the creation of new new media that create a new audience – prosumers. New new media enable users to produce and consume content at the same time. It is precisely this dynamic that characterises the rise of influencers. Influencers or creators of public opinion are not a novelty, but unlike influencers in the past – royalty, nobility, political elite, athletes and others – today's influential persons gain their popularity and influence largely thanks to the development of technology, and they shape audience attitudes through the creation of announcements, vblogs, tweets and other online social media channels. In this paper, the language of influencers' is analysed in two categories: lexical and syntactic. The methodological framework is centred on a qualitative method of content analysis that can be quantified. This is a research technique used to classify and describe communication content according to predetermined categories, i.e. the communication is analysed in a systematic and quantitative way. Following the study carried out by Styria and the Nielsen agency, a research sample was defined using the NielsenMedia methodology and the InfluenceScope tool (2021).